Climate change and eHealth: a promising strategy for health sector mitigation and adaptation - Åsa Holmner; Joacim Rocklöv; Nawi Ng; Maria Nilsson (Taylor & Francis Group, 2012)
Climate change is one of today's most pressing global issues. Policies to guide mitigation and adaptation are needed to avoid the devastating impacts of climate change. The health sector is a significant contributor to greenhouse gas emissions in developed countries, and its climate impact in low-income countries is growing steadily. This paper reviews and discusses the literature regarding health sector mitigation potential, known and hypothetical co-benefits, and the potential of health information technology, such as eHealth, in climate change mitigation and adaptation. The promising role of eHealth as an adaptation strategy to reduce societal vulnerability to climate change, and the link's between mitigation and adaptation, are also discussed. The topic of environmental eHealth has gained little attention to date, despite its potential to contribute to more sustainable and green health care. A growing number of local and global initiatives on ‘green information and communication technology (ICT)’ are now mentioning eHealth as a promising technology with the potential to reduce emission rates from ICT use. However, the embracing of eHealth is slow because of limitations in technological infrastructure, capacity and political will. Further research on potential emissions reductions and co-benefits with green ICT, in terms of health outcomes and economic effectiveness, would be valuable to guide development and implementation of eHealth in health sector mitigation and adaptation policies.